2021
DOI: 10.3389/fnins.2021.617443
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Is Not a Benzo: Distinctive Associations of Heart Rate Variability With Its Empathic and Action Components

Abstract: Recent studies have linked compassion with higher vagally mediated heart rate variability (vmHRV), a measure of parasympathetic activity, and meta-analytic evidence confirmed significant and positive associations. Compassion, however, is not to be confused with soothing positive emotions: in order to engage in actions aimed to alleviate (self or others) suffering, the pain should resonate, and empathic sensitivity should be experienced first. The present study examined the association between vmHRV and the emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…The present study also aimed to explore the impact of the CMT-T on heart rate variability (HRV), an indicator of vagal regulatory activity and a physiological marker of a person’s ability to flexibly respond to environmental challenges and regulate emotional responses [ 40 , 50 , 75 ], which has been proposed as a primary measure to assess and train compassion [ 44 , 56 ]. Results showed that HRV significantly increased in the CMT-T group from baseline (T1) to post-intervention (T2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study also aimed to explore the impact of the CMT-T on heart rate variability (HRV), an indicator of vagal regulatory activity and a physiological marker of a person’s ability to flexibly respond to environmental challenges and regulate emotional responses [ 40 , 50 , 75 ], which has been proposed as a primary measure to assess and train compassion [ 44 , 56 ]. Results showed that HRV significantly increased in the CMT-T group from baseline (T1) to post-intervention (T2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compassion positively impacts physiological health, including influences in genetic expression [e.g., lower levels of CTRA-related gene expression, 48 ; epigenetic profiles of the OXTR, 49 ]. Experimental studies have also documented that cultivating compassion impacts physiological systems, reducing arousal and increasing parasympathetic activation [e.g., heart-rate variability, HRV, 50 53 ], decreasing sensitivity to threat [ 49 ], and activating specific neural circuits distinct from empathy and mindfulness training [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…One-hundred and seventy-two healthy individuals, whose resting vmHRV was assessed between May 2018 and October 2019 (Time 0; T0) during participation in previous studies (16)(17)(18)(19), were recruited. Specific information about vmHRV assessment can be found in the original studies (16)(17)(18)(19).…”
Section: Methodsmentioning
confidence: 99%
“…One-hundred and seventy-two healthy individuals, whose resting vmHRV was assessed between May 2018 and October 2019 (Time 0; T0) during participation in previous studies (16)(17)(18)(19), were recruited. Specific information about vmHRV assessment can be found in the original studies (16)(17)(18)(19). After the exclusion of 2 participants with current diagnosis of medical disorders, a total of 69 individuals were considered for this investigation, which includes data Next, participants were asked to download a free-avilable smartphone application (https://ecg4everybody.com/) and instructed to record vmHRV using finger tip photoplethysmography under resting conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation